Assessing UGFS+SFL as an Alternative to Conventional Surgery for Varicose Veins: Outcomes, Safety, and Economic Implications: A Comparative Study - Majeed , Ahmed Salman; Mashhood , Hafiz Muhammad; Naseem , Muhammad Huzaifa; Ashraf, Maham; Ashal Pal, Mujtaba; Saeed, Kanwal; Qammar , Bilal (Indus Journal of Bioscience Research, 2024)
Objective: The aims of the study is to compare the efficacy, safety, and the cost-effectiveness of ultrasound-guided foam sclerotherapy related with the sapheno-femoral ligation (UGFS+SFL) versus conventional surgical treatment for the varicose veins.Methods:  This study was conducted over a period of 18 months. Minimum of 80 patients with primary varicose vein due to SFJ (saphenofemoral junction) incompetence were selected and randomly assigned in each arm i.e. surgical and foam sclerotherapy.Results: Both of UGFS+SFL and the conventional surgery led to the significant improvements in CEAP and the VCSS scores. UGFS+SFL group showed the greater reduction in VCSS scores post-treatment compared to surgical group. The Early complications were fewer in UGFS+SFL group, which had no cases of deep the vein thrombosis (DVT) or saphenous nerve injury, the unlike surgical group. Cost of UGFS+SFL was Rs.255924, the significantly lower than Rs.425644 for conventional surgery. The Ultrasound follow-up revealed high rates of vein obliteration in the both groups, though UGFS+SFL group had slightly the lower rates of full obliteration at 3 months.Conclusion: The UGFS+SFL is an effective and the cost-effective alternative to conventional surgery for treating the varicose veins. It offers the comparable clinical outcomes with fewer complications and the lower costs. These treatments achieve high rates of the vein obliteration, making UGFS+SFL a viable option for patients seeking the less invasive approach